2009
DOI: 10.1124/jpet.109.159020
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Glycolates Antagonize CXCR2 Activity through an Intracellular Mechanism

Abstract: The chemokine receptors CXCR1/2 are involved in a variety of inflammatory diseases, including chronic obstructive pulmonary disease. Several classes of allosteric small-molecule CXCR1/2 antagonists have been developed. The data presented here describe the cellular pharmacology of the acid and ester forms of the nicotinamide glycolate pharmacophore, a potent antagonist of CXCR2 signaling by the chemokines CXCL1 and CXCL8. H acid was not internalized by neutrophils but was sufficient alone to inhibit CXCL1-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Recent research has focused in developing antagonist with a mechanism of allosteric inhibition rather than competition. A drug discovery program aimed only at CXCR2 has focused on the nicotinamide glycolate pharmacophore [88]. It is based on the notion that distinct allosteric antagonist sites exist on CXCR2 [89].…”
Section: Chemokine Receptorsmentioning
confidence: 99%
“…Recent research has focused in developing antagonist with a mechanism of allosteric inhibition rather than competition. A drug discovery program aimed only at CXCR2 has focused on the nicotinamide glycolate pharmacophore [88]. It is based on the notion that distinct allosteric antagonist sites exist on CXCR2 [89].…”
Section: Chemokine Receptorsmentioning
confidence: 99%
“…Abnormal accumulation and biosynthesis of melanin pigments are responsible for hyperpigmentation disorders such as melasma, freckles and senile lentigo. These can be substantially ameliorated by treatment with arbutin or other tyrosinase inhibitors (13,14). Manassantin A (Fig.…”
Section: Question Addressedmentioning
confidence: 99%
“… 34 We have previously shown that CXCR2 antagonism by nicotinamide glycolate esters proceeded through a novel intracellular mechanism that required hydrolytic cleavage of the ester within the neutrophil for activity. 35 However, the unique pharmacology of this class also led to rapid degradation in plasma, making it untenable as a therapeutic. The mechanistic insights gleaned from these studies inspired us to search for new nicotinamide templates that would directly antagonize CXCR2 without requiring intracellular hydrolytic activation for their activity.…”
Section: Introductionmentioning
confidence: 99%